Pengetahuan Kepada Ibu Balita Terhadap Bahaya Stunting Dan Cara Pencegahannya Di Desa Kepau Jaya Kecamatan Siak Hulu Kabupaten Kampar - Dian Oktary; Fabian Ahmad Bimantara; Fathurrahman Adam Rahadian; Annisya Madani; Almaqviroh Almaqviroh; Diny Olivia; Riska Amalia; Manda Fatimah Sari; Attisyah Saharumni; Sri Rahmadani (FKIP, Universitas Palangka Raya, 2023)
Stunting is a condition of chronic malnutrition due to malnutrition over a long period of time, causing growth disorders in children, meaning that the child's height is lower or shorter (does not grow strong) compared to children of the age standard. The physical and mental growth and development of children can cause developmental delays in children. The risk of disease and death as well as delays in the development of children's motor and mental abilities are closely related to developmental delays. If it is not addressed, the problem of stunting will arise, which is considered to be a result of malnutrition, a serious problem for a country, namely hampering a country's development because its human resources are of poor quality (Fauza et al., 2022). For this reason, joint efforts are urgently needed to resolve the stunting problem in Indonesia. Socialization is an effort carried out by the Kubang Jaya Community Health Center which is the first step taken to overcome the Stunting phenomenon among the community in Kepau Jaya Village, Siak Hulu District, Kampar Regency. This socialization was attended by PKK mothers, pregnant mothers, mothers with babies under 5 years old, as well as the KUKERTA team from Kepau Jaya Village. The delivery of socialization concerns the causes of stunting, how to overcome it, and how to avoid stunting. The benefit of this activity is providing all the information and understanding to mothers in Kepau Jaya Village. By conducting outreach activities to mothers of toddlers about the dangers of stunting and how to prevent it and creating a program to provide basic necessities to prevent stunting in children. This program can be used to overcome the stunting phenomenon that occurs in communities in Kepau Jaya Village, Siak Hulu District, Kampar Regency. Every parent must be aware of the dangers of stunting in children which can hinder the child's further growth and development.